FACTORS RELATED TO MENTAL HEALTH PROBLEMS IN BACHELOR STUDENTS OF PUBLIC HEALTH: Faktor-Faktor Yang Berhubungan Dengan Masalah Kesehatan Mental Pada Mahasiswa Sarjana Kesehatan Masyarakat - Bastira Ginting, Johannes; Karo-Karo, Styfani; Ayu Suntiarma Situmeang, Hasnita; Mustika Ananda, Putri; Hartono, Hartono (Jurnal Berkala Epidemiologi, 2025)
Background: Mental health is the ability to realize one’s potential and cope with the usual demands of daily life. Students in Public Health programs are especially at risk of developing mental health problems while studying as a result of academic stress. This study explored the factors related to mental health problems among the Bachelor of Public Health students at Universitas Prima Indonesia. Methods: This survey research is quantitative, and a cross-sectional design was employed. The population of this study was all Bachelor of Public Health students in the even semester of the year 2023/2024 at FKKGIK, Universitas Prima Indonesia. Primary data were collected using questionnaires, and secondary data included scientific articles and research papers published within the last 5-10 years. Univariate, bivariate, and multivariate data analysis was done. Results: The study found a positive correlation between academic pressure, interpersonal relations, learning strategies, social relations, individual motivation, group interactions, psychological well-being, and the severity of mental health problems among undergraduate public health students (p-value ≤ 0.05). However, the study's findings showed that gender, semester, place of residence, and psychological pressure have no relationship (p-value > 0.05). Conclusion: These results indicate that social and academic factors should be considered to promote students' mental health. Therefore, universities should design strategies to address these essential factors to support students’ mental health and learning achievements.